Improved control on the morphology and LSPR properties of plasmonic Pt NPs through enhanced solid state dewetting by using a sacrificial indium layer. Issue 4 (17th January 2019) - Kunwar, Sundar; Sui, Mao; Pandey, Puran; Gu, Zenan; Pandit, Sanchaya; Lee, Jihoon
Abstract : Fabrication of Pt NPs with the improved configuration, spacing, uniformity and localized surface plasmon resonance (LSPR) response is demonstrated. Abstract : Platinum (Pt) nanoparticles (NPs) are important nano-material components in various catalytic, photonic and electronic applications, yet face challenges in the fabrication of desired morphology and uniformity with the conventional solid-state dewetting approach. Specifically, the necessity of high annealing temperatures, typically above 800 °C due to the low diffusivity of Pt atoms, limits the morphological and functional tunability of Pt NPs. In this work, the fabrication of Pt NPs with an improved configuration, spacing and uniformity is demonstrated through the enhancement of solid state dewetting by using a sacrificial indium (In) layer on sapphire (0001). The well-defined Pt NPs demonstrate the dynamic localized surface plasmon (LSPR) bands in the visible range between ∼400 and 700 nm depending on the size and spacing of NPs. The LSPR peak intensity and width are also varied depending on the uniformity of Pt NPs. The overall dewetting magnitude is significantly enhanced through the inter-mixing of In and Pt atoms at the In/Pt interface that eventually results in the formation of an In–Pt alloy. During the dewetting process the In atoms desorb from the NP matrix by atomic sublimation, which gives rise to pure Pt NP fabrication. In sharp contrast to the pure Pt film dewetting, the Pt NPs in this approach demonstrate significantly improved spatial arrangement with well-defined configuration and uniformity. In addition, the ratio of In can be readily controlled along with the thickness of the Pt layer to alter the dewetting kinetics and thereby the surface morphology of Pt NPs. Specifically, large hexagonal, semi-spherical and small hexagonal Pt NPs are obtained through the dewetting of In75 nm /Pt25 nm, In20 nm /Pt20 nm and In2.5 nm /Pt7.5 nm bilayers respectively.